BIMBINGAN DAN PENGARAHAN TENTANG KIAT SUKSES MEMULAI USAHA DI BIDANG MAKANAN PKK RT 13 RW 08 KELURAHAN BARENG KECAMATAN KLOJEN KOTA MALANG - Shinta Maharani Trivena; Rena Feri Wijayanti; Lina Budiarti; Tri Yulistyawati Evelina; Nilawati Fiernaningsih (Jurnal Pengabdian Polinema Kepada Masyarakat, 2020)
This Community Service activity was held on Sunday 3 May 2019 in PKK RT 13 RW 8 Bareng, Klojen District Malang City. This activity is divided into several stages, namely the preparation stage, including the preparation of places and events, the stage of material delivery, the discussion stage, and the closing stage. The goals achieved are to To open trainees' insights that opportunities around are potential to be utilized so that they can produce economic value. The success in community service can be seen from the enthusiasm of the trainees who are actively discussing and asking questions. The activity was attended by almost all PKK management and members. Participants want on going activities.